Real-Time Visibility for Building Adaptive Resilience - Wycislak, Slawomir; Akhtar, Atif (International Journal of Supply Chain Management, 2025)
Supply chain resilience has become critical in today's volatile global landscape. Recent disruptions have exposed vulnerabilities in interconnected supply networks, highlighting the need for new approaches to managing complex, rapidly evolving challenges. This research investigates how real-time visibility facilitates adaptive resilience in global supply chains through an integrated theoretical framework. Using a mixed- method approach, we analyze five major recent supply chain disruptions including the Red Sea crisis, Panama Canal drought, COVID-19 outbreaks, Baltimore bridge collapse, Israel-Iran conflict. We develop the Real-Time Adaptive Resilience (RTAR) model, a four- layer framework that explains how visibility transforms data into adaptive capabilities. Our findings reveal three key mechanisms through which real-time visibility enhances resilience: information velocity, system-wide transparency, and predictive capability. The research contributes to supply chain management theory by integrating Resource-Based View, Dynamic Capabilities, and Systems Dynamics perspectives while providing practical guidance for building adaptive supply chain capabilities.